The Relationship of Scouting Extracurricular Education and Parenting Patterns with Student Discipline Characters - Senjani, Estri Dwi; Widodo, Susilo Tri (Elementary School Teacher, 2021)
This study aims to test and prove whether there was a relationship between scouting extracurricular activities andparenting styles with the formation of disciplinary character for the 5 grade students of the Gugus Mawardhi. The methodused in this research is correlation. Data collection techniques used were observation, interviews, documentation andquestionnaires. The prerequisite tests carried out were the normality test, linearity test, reliability test, andmulticollinearity test. The data analysis technique used descriptive analysis, simple correlation, multiple correlation, andthe F-test. The results showed that there was a positive and significant relationship between scout educationextracurricular activities with the formation of disciplinary character in grade 5 elementary school students. The resultsshowed that rcount was greater than rtable, namely 0.5290.179 with a significance level of 5%. The results showed thatrcount was greater than rtable, namely 0.6370.179 with a significance level of 5%.. These results indicate rcount isgreater than r table, namely 0.677 0.179 with a significance level of 5%, the relationship between the scoutsextracurricular education variables and the formation of disciplinary character is in the moderate category. The results ofthe percentage of student questionnaire responses showed a very positive relationship between scouting extracurricularactivities, parenting styles, and the character of student discipline simultaneously.Keywords: scouting, parenting style, discipline